Current state and the support system of athlete wellbeing in Japan: The perspectives of the university student-athletes - Noguchi, Yoriko; Kuribayashi, Chisato; Kinugasa, Taisuke (Frontiers in Psychology, 2022)
The optimization of athlete well-being has been increasingly considered important both in academic and practical fields of high performance sport. Various organizations such as the International Olympic Committee have promoted its importance particularly focused on mental health. Moreover, the increased attention to athlete well-being in sport policy debate at the national level has led to development and implementation of the support system for athlete well-being in some countries. Nevertheless, the literature is limited to understand the case of Japan. Interestingly, only 0.8% of literatures available on “athlete” and “well-being” in Japanese compared to English journals up to 2019. Therefore, the purpose of this study was to identify (a) the current state of well-being with Japanese university student-athletes, (b) the level of knowledge about athlete well-being, (c) the athletes’ perception on the availability of well-being support in the national sport federations, (d) the athlete experience of support services, and develop the types of national supports athletes expect and need from government and national sport federations in the future. As a pilot study, a total of 100 Japanese university student-athletes (43 male, 57 female) from 17 Olympic and 7 Paralympic sports completed an online survey. Consequently, the state of their well-being was self-perceived relatively good in all dimensions (i.e., physical, mental, educational, organizational, social, and financial). Moreover, the results showed low recognition of the term “athlete well-being,” as well as the lack of knowledge in the availability and accessibility to appropriate support services. The results also showed that the Japanese university student-athletes rarely seek help to experts while 45% indicated “no one” to talk to. Interestingly, however, most athletes considered each dimension of well-being important in relation to their performance development. Based on the results, it is necessary to develop education program, guidelines, detection system, and improve information accessibility. Givens the validity, reliability, and feasibility of this pilot study were verified, further studies should focus more on well-being of Japanese elite athletes in high performance sport (i.e., Olympic and Paralympic athletes).